Spiritual Leadership, Internal Marketing, and Organizational Citizenship Behavior: A Conceptual Review for Islamic Educational Institutions - Sutanpri, Sutanpri; Abdillah, Willy; Salim, Muhartini; Hayu, Rina Suthia (Strata Business Review, 2025)
This conceptual study explores the interrelationships among spiritual leadership, internal marketing, and organizational citizenship behavior (OCB) within Islamic educational institutions. Utilizing a narrative literature review of 32 peer-reviewed publications spanning 2000–2024, the paper synthesizes theoretical and empirical insights to clarify how spiritually grounded leadership practices shape employees’ attitudinal and behavioral outcomes. The review identifies spiritual leadership as a values-based framework that promotes meaning, purpose, and ethical direction in organizational settings, yet prior studies reveal inconsistencies regarding its direct influence on OCB, indicating the potential role of mediating variables. Internal marketing is proposed as a strategic mechanism that aligns institutional values with employee experience, strengthens motivation, and enhances prosocial behaviors such as OCB. Drawing on Social Exchange Theory and the Stimulus–Organism–Response (SOR) model, this paper introduces a conceptual framework positioning internal marketing as a mediator between spiritual leadership and OCB, thereby addressing a significant gap in the literature. The proposed model offers practical implications for leaders seeking to cultivate spiritually grounded, value-driven, and performance-oriented cultures in Islamic educational environments while providing a foundation for future empirical validation.